Dataset on varietal preferences, gender roles, and rainfall variability in wheat seed systems in Ethiopia - Gartaula, Hom; Gebremariam, Gebrelibanos; Jaleta, Moti (Elsevier, 2025)
This dataset provides household-and plot-level information on wheat farmers in Ethiopia, with a focus on gender dynamics, rainfall variability, and farmers' preferences for wheat varietal traits. The survey was implemented in 2021 by the International Maize and Wheat Improvement Center (CIM-MYT) under the Accelerating Genetic Gains in Wheat (AGG) project and covered 1,088 households across the country's major wheat-growing regions. The questionnaire included modules on household demographics, farm and plot characteristics, wheat production practices, varietal adoption and seed sourcing, gendered decision-making, access to extension services, social capital and networking, food security, dietary diversity, and health. It also documents farmers' preferences for key varietal traits, including yield potential, drought tolerance, disease resistance, straw yield, baking quality, and nutritional attributes. Household GPS coordinates were used to link survey responses with high-resolution rainfall data, enabling analysis of climate variability and its interaction with household and farm-level outcomes. This dataset provides a valuable resource for researchers and policymakers to examine how gender roles and agroecological conditions shape demand for wheat traits, with implications for designing climate-resilient and gender-responsive seed system interventions in Ethiopia.